Management control systems and organisational learning: the effects of design and use. Issue 2 (19th August 2014) - Wee, Shu Hui; Foong, Soon Yau; Tse, Michael S. C.
Abstract : Purpose: This paper presents a study on relationships between the design of management control systems (MCS), the use of MCS and organisational learning (OL). Design/methodology/approach: This study adopted a survey method. A written questionnaire was prepared and mailed out to collect quantitative data. After analysis of the empirical results, follow-up interviews were conducted to develop a deeper understanding of the empirical results. Findings: Findings of the study show that both the design and use of MCS are significantly associated with levels of OL activities in organisations, and the use of MCS is found to be a more influential factor in OL. Originality/value: This paper contributes to the accounting literature by providing empirical evidence on the relative impacts of the design and use of MCS on OL activities in organisations, and the interaction between the design and use of MCS in influencing OL.